DIVERSION FUNCTION OF WAQF LAND USE (Review of Islamic Law and Acts No. 41 Year 2004) - nilam sari (Al-Qalam, 2018)
Benefaction is one of facility to increase quality and quantity of worship to Allah has a main foundation that was Al-Qur’an and hadits, because as worship, benefaction has regulated for its legal requirement by Allah SWT. The provisions of benefaction and other worships that will performed by human being as means to close him selves to Allah. This article discussed about stipulation of diversion of benefaction property function according to stipulation of Islamic law (fiqh) and laws No. 41 Year 2004 concerning to benefaction. Related to diversion of function of benefaction property use have happened some perspectives among of several theologians, there was part of theologian prohibited to change function and advantage of such benefaction of property, when such benefaction property in form of a building such as mosque, house and others. But in other hand, some theologians allowed change of function of waqf land during its original form do not changed and it not change to other name of such benefaction property. Such benefaction property which has diverse should be more strategic property, productive and empowered for religion and Islam community. Difference between Islamic law (fiqh) and positive law concerning to diversion of benefaction property function where in provision of fiqh jumhur of theologian was allowed the diversion of benefaction property function so long as do not change purpose of benefaction and do not change the object name which has donated. While the positive law was not regard such things, substantially it fulfilled economic value and productive and it not in opposition to law of sharia provision.